Sistem Pemasaran Gula Semut Kelompok Tani Hutan (KTH) Buhung Lali Pada Hutan Kemasyarakatan (HKm) Bangkeng Bukit di Desa Bukit Harapan Kecamatan Gantarang, Kabupaten Bulukumba - Anna Cristine Mokuna; Makkarennu Makkarennu; Ridwan Ridwan (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Palm sugar is one of the potential products of Non-Timber Forest Products (NTFPs) that can contribute to increasing farmers' income and welfare, especially for communities around the forest. This study aims to identify marketing system of palm sugar at Community-based Forest in Bulukumba Regency. This research applied interview, observation, and study-literature methods. The samples selected by purposive sampling were the farmers in the Bangkeng HKm Bukit Harapan village and the traders of the palm sugar in Makassar. Then, from these samples, the market margin, the farmer share and the profit of trade agencies were descriptively and quantitative analyses. The results show that there are three marketing channels of the palm sugar trade in Bukit Harapan village i.e farmers directly to costumers, farmers to retailers to customers, and from farmers to the whole seller to customers. In the first channel, farmers to customers, there are the market distortions like monopoly, transaction cost, externalization, and public goods. In the second channel, farmers to retailers to customers, the market distortions found in this path are oligopoly and externalization. In the last channel, the market distortions are monopsony and transaction cost. Based on the analysis, it is found that the highest the market margin and the most profitable lines are the first and the third lines with the profit to 100% because the higher the value of farmer share, the better and more efficient the market performance